Endangered Land Snails of the Eastern United States - Leslie Hubricht (Hello World!, 1972)
Listed below are the land snails of the eastern United States which because of restricted ranges or other factors could readily become extinct should adverse conditions arise. Most of the species are known only from a single locality. Others are found in areas which are undergoing rapid development with destruction of their habitats, such as the Florida Keys.